Strategy for Business Development of Community Food Barn in South OKU District - Budi, Julian Setia; Munajat, Munajat; Efrianti, Rini (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2022)
Indonesia is known as an agricultural country that has diverse natural resource potential. However, Indonesia is facing a serious problem in terms of food which is the basic need of everyone. Food problems can be in the form of excess food, food shortages, household inability to meet food needs, and emergencies. One of the problems faced by Indonesia is food insecurity or food shortages which are closely related to poverty. One of the development focuses at the moment is directed at addressing the problems of food insecurity and poverty by improving food security. The Food Barn Business Development activity is one of the government's efforts to maintain price stability both at the farmer/producer level and at the consumer level. Through this activity, the Food Barn Group is empowered to be able to carry out its function as a distribution institution in a more efficient distribution chain to reduce price disparities between producers and consumers and indirectly play a role in overcoming plummeting prices during the harvest period and high prices during famine and become an instrument made by the government to withstand price fluctuations in certain situations. Based on the research that has been carried out, the strategies that should be carried out for the Development of a Food Barn Business in South Ogan Komering Ulu District.